Analysis of the State and Characteristics of the Development Potential of Strategic Planning Tools in the Digital Transformation Conditions of the Economy and Management - O. M. Pisareva (Модернизация, инновация, развитие, 2019)
Purpose: the purpose of the study is to determine the main directions and conceptual approaches to modernizing analytical and computer support for the planning of strategic development of socio-economic systems on a national scale in the framework of improving the methodology of strategic planning in a digital transformation of the economy and management.Methods: the issues of improving the tools of strategic planning of socio-economic development are studied in the framework of a system approach to analyzing the construction and functioning of the state management mechanism in the context of active formation of the information society infrastructure and to evaluating of the impact of digital technologies on the content of management tasks in the process of co-evolution of objects and subjects of management in large-scale organizational systems.Results: the article deals with current problems and key tasks of modernization of scientific and methodological, informational and analytical support of state strategic management of socio-economic development. The trends of the evolution of objects and subjects of management in the conditions of the digital transformation of the information society are investigated. The institutional bases for the construction and operation of the strategic planning system of the Russian Federation are characterized. A block diagram of a complex of heterogeneous models of strategic planning of socio-economic development is given. Design solutions are proposed for building the architecture and developing a prototype of the computer support system for the scenario modeling technology when developing multi-level strategic decisions for planning socio-economic development in the emerging infrastructure of the digital economy is presented.Conclusions and Relevance: the study showed the importance and relevance of modernization of the methodological and analytical support of the strategic planning system of the Russian Federation, which takes into account the main consequences and requirements of the creation and distribution of digital technologies in various areas of society. The most important characteristics of innovative changes in the structure and content of strategic planning tasks, the solution of which is associated with the unification of the format of quantitative and qualitative assessments in the digital development management environment, are identified. Standardization of technologies for collecting, transmitting, storing and processing large amounts of data allows you to build computer software for the multi-level system of state strategic planning based on an open service-oriented architecture. The main direction of further research and development in the creation of an analytical platform to support strategic planning of socio-economic development can be the creation of a mathematical apparatus and software products for processing and analyzing large amounts of personalized information about the functioning of economic and social agents to identify and assess their potentials and priorities. This will allow to increase the degree of justification and consistency of planned decisions and regulatory measures developed by the state in the field of planning socio-economic development and ensuring the national security of the Russian Federation.